أزمة الماء وآفاق استدامته بالمناطق الجافة، وشبه الجافة بالمغرب واحة فركلة بحوض غريس أنموذجاً (مجلة جامعة سرت للعلوم الانسانية, 2023)
The Drinking water is considered an essential criterion in the development of any country or region, and its availability means stability for the population and their avoidance of diseases resulting from the water problem, which causes many deaths. That is why the search for safe drinking water and its long-term guarantee was an actual recognition of real sustainable development that guarantees human survival and continuity and thus improves the standard of living. The demand for water increases with the growth of the population, especially the urban population, which doubles the needs, especially with the multiplication of the requirements of modern life.The problem of managing water resources is further raised in the oasis areas, especially in tafilanlt, because the lack of water resources destined for drinking, their mismanagement and exploitation, in addition to the deterioration of their quality, would negatively affect the living and health conditions of the population and sometimes threaten even their stability in these areas.
Keywords: Morocco; Water resource; Oasis Ferkla; Water scarcity; Adaptation